Muzyka i medium. Szkic historiograficzny od początków do dzisiaj - Faulstich, Werner (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2010)
The relationship between music and media is closer than it is obvious at first sight. That includes primary media such as the singer or the theatre performance of an opera, print media such as sheet music and music books, electronic media like the record, the tape, radio, film and television, and the recent digital media such as the world wide web, the compact disc or the i-pod. If turned historically, we can realize a chain of media expressing and describing the history of music – from the ancient priestess and singers over the aoide and the rhapsode in old Greek culture presenting epic poetry and narrative literature up to church and choir singers in Christian churches, from mine singers, hymnbooks and troubadours in the Middle Ages up to ballad singers and street musicians selling music sheets and books in the 18th century, from music performance as live music up to recorded and canned music and finally a kind of quarry music allowing everyone a subjective and eclectic selection. The functional history of music follows inevitably the history of media.
Keywords: Primary media; Print media; Electronic media; Singer; Music performance; Recorded music; Quarry music